Utilização de implante ósseo cortical alógeno conservado em glicerina para preservação de membro torácico: estudo experimental em cães - Ziliotto, Liane [UNESP]; Daleck, Carlos Roberto [UNESP]; Padilha Filho, João Guilherme [UNESP]; Souza, Almir Pereira De; Fantinatti, Alexandra Pinheiro [UNESP]; Diniz, Pedro Paulo Vissotto De Paiva (Sociedade Brasileira para o Desenvolvimento da Pesquisa em Cirurgia, 2003)
A limb-sparing surgery can be an alternative treatment to amputation for dogs with appendicular osteosarcoma. PURPOSE: The purpose of this study was the development of this surgical technique, similar to the original, described by Straw¹, with changes in the procedure of the allografts preservation, and in the bone cement chose to be used intramedullary. METHODS: The surgery was performed in six health dogs, with the osteotomy of one-third of the radio and ulna, section of the distal margin in the radio-carpal joint and reconstruction using a cortical allograft preserved in 98% glycerin. The allograft's medullar channel was filled with a polymer extracted from castor oil (Ricinus communis) and a long dynamic compression plate were used to fix this allograft on the radio, carpal joint and 3rd metacarpal bone, with the arthrodesis of the carpal joint. A medio-lateral radiographs was performed immediately posteoperatively and with 7, 15, 30, 45, 60, 90, 120 and 150 days after surgery, to evaluate the allograft incorporation. The histopatological evaluation was done with 90, 120 and 150 days after surgery. RESULTS: Was notice a bone callus formation on the radiogrhphs exams by 60 days after surgery and bone bridges were closing the interfragmentary space, with remodeling by 90 days. We have noticed resorption of the grapht, with formation of a connective tissue and new bone around the polymer on the histophatological evaluation. A neovascularization and inflammatory cells in the connective tissue was noticed with a decreased in the inflammatory process with the time. CONCLUSIONS: The polymer extracted from castor oil showed to be a good substitute for the bone cement originally used in the limb-sparing surgery, increasing the graft resistance with no foreign body reaction or osteointegration. The allograft preserved in glycerin presented onteoinduction and osteocondution actions, with new bone formation, and no signs of rejection, then, the glycerin showed to be a good alternative preservation procedure. Therefore, the modified technique can be considered an alternative to the original limb-sparing surgery and to amputation for dogs with appendicular osteosarcoma, studies still deserve to be done with sick animals.

A técnica de preservação de membro é uma alternativa à amputação em cães com osteossarcoma do esqueleto apendicular. OBJETIVO: O desenvolvimento da técnica preservadora aos moldes da original descrita por Straw¹. MÉTODOS: O procedimento cirúrgico foi realizado com modificações, substituindo-se o método de conservação dos implantes pela glicerina e o cimento ósseo utilizado no preenchimento do canal medular do implante pela poliuretana de mamona, e para avaliação da incorporação do implante foram feitos exames clínico, radiográfico e histopatológico em diferentes tempos pós-operatórios. RESULTADOS: Observada a boa função do membro no pós-operatório, a formação de calo ósseo e fechamento das linhas de interfaces com remodelação óssea em avaliação radiográfica e ao exame histopatológico foi notada a reabsorção do implante ósseo com sua substituição por tecido conjuntivo fibroso e tecido ósseo compacto, neovascularização e presença de infiltrado inflamatório plasmocitário. CONCLUSÕES: A poliuretana de mamona mostrou-se uma boa substituta ao cimento originalmente utilizado, aumentando a resistência do implante, sem causar reações do tipo corpo estranho e sem sua osteointegração. O implante ósseo conservado em glicerina apresentou ação osteoindutora e osteocondutora, sem sinais de rejeição; desta forma, a glicerina mostrou ser uma meio alternativo viável. Portanto, a técnica de preservação do membro, com suas modificações, caracterizou-se como alternativa à técnica original e à amputação do membro para cães com osteossarcoma de esqueleto apendicular.
A limb sparing surgery with the use of a cortical allograft preserved in glicerin: an experimental study in dogs
Keywords: Osteosarcoma; Glycerin; Polymer extracted from castor oil; Limb-sparing; Cortical allograft; Osteossacoma; Glicerina; Poliuretana de mamona; Preservação de membro; Implante ósseo